Characteristics and Risk Factors of Children Requiring Prolonged Mechanical Ventilation vs. Non-prolonged Mechanical Ventilation in the PICU: A Prospective Single-Center Study - Liu, Yanling; Wang, Qingyue; Hu, Jun; Zhou, Fang; Liu, Chengjun; Li, Jing; Fu, Yueqiang; Dang, Hongxing (Frontiers in Pediatrics, 2022)
Background: Prolonged mechanical ventilation (PMV) has become an enormous challenge in intensive care units (ICUs) around the world. The status of children who have undergone PMV is unknown. Our goal is to investigate the prevalence and characteristics of pediatric patients with PMV, as well as the risk factors of PMV in the pediatric intensive care unit (PICU). Methods: The subjects were divided into two groups, the PMV group and the non-PMV group, in light of the duration of mechanical ventilation. The baseline characteristics, treatments, and results between the two groups were compared. The risk factors associated with PMV were evaluated using univariate and multivariable analyses. Results: Of the 382 children enrolled, 127 (33.2%) received PMV. The most common cause of mechanical ventilation in the PMV group was acute lung disease (48.0%), followed by acute circulatory system disease (26.0%), acute neurological disease (15.0%), postoperative monitoring (10.2%). Comorbidities were more prevalent among the PMV group (P=0.004). The patients with PMV had a higher rate of premature birth (24.4% vs 14.1%, P=0.013) and higher PIM3 scores at admission (5.6(3.0-9.9) vs 4.1(1.7-5.5), P<0.001). The use of inotropes/vasopressors (63.8% vs 43.1%, P<0.001) was more common in patients with PMV compared with those in the non-PMV group. In the PMV group, the extubation failure rate (39.4% vs 6.7%, P<0.001) was higher than in the non-PMV group. The median hospital stay, PICU stay, hospitalization costs, and mortality after 1-month discharge (22.0% vs 1.6%, P<0.001) were higher in the PMV group. Multivariate analysis revealed that age < 1 year old, a higher PIM3 score at admission, premature birth, the use inotropes/vasopressors, extubation failure, and ventilator mode on the first day of MV were associated with PMV. Conclusions：The incidence and mortality of with PMV in pediatric patients is surprisingly high. Premature infants or patients with severe disease or extubation failure are at higher risk of PMV. Patients with PMV exhibited a higher burden of illness and higher hospital costs than those on non-prolonged mechanical ventilation. It is important to establish specialized weaning units for mechanically ventilated patients with stable conditions.